Engineering biocompatible benzodithiophene-based polymer dots with tunable absorptions as high-efficiency theranostic agents for multiscale photoacoustic imaging-guided photothermal therapy. (23rd January 2019) - Chang, Kaiwen; Gao, Duyang; Qi, Qiaofang; Liu, Yubin; Yuan, Zhen
Abstract : Conjugated polymer dots with tunable absorptions by controlling the structure have been engineered for multiscale photoacoustic imaging-guided photothermal therapy. Abstract : To date, photoacoustic imaging (PAI) and PAI-guided photothermal therapy (PTT) have been performed for noninvasive cancer diagnosis and precise ablation of tumors. To conduct concurrent PAI and PTT, it is essential to develop theranostic agents with strong optical absorption and high photothermal transfer efficiency. In this study, we have engineered theranostic agents with tunable absorptions based on conjugated polymer dots (Pdots) with different structures via the simple precipitation method. The as-synthesized Pdots exhibit strong absorption, high biocompatibility, and superior stability. In addition, the Pdots demonstrate that they can serve as contrast agents for multiscale PAI in vitro and in vivo . More importantly, a high photothermal conversion efficiency up to 40% is reached under irradiation with LED light, resulting in effective cancer treatment with extremely low light dose. Consequently, they show the potential as imaging-guided therapeutic agents for clinical cancer treatment and various biomedical applications.